Comparative Effectiveness of Narrative and Informational Content for Audience Engagement in Educational Social Media: A Systematic Literature Review - Adi Mulya; Nabil Muttaqin; Dwi Soca Baskara; Dio Lingga Purwodani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This systematic literature review examines the comparative effectiveness of narrative-based versus traditional informational content in fostering audience engagement across educational social media platforms. Findings consistently indicate that narrative-based and visually engaging content outperforms traditional, text-based formats regarding likes, shares, comments, and overall audience retention. Posts incorporating personal stories, interviews, and dynamic visuals on Facebook and Instagram attracted significantly higher interaction than expository or lecture-style formats. Similarly, on Twitter, visual abstracts and infographics yielded 2.75 and 2.06 times greater engagement than traditional text-based posts. YouTube videos employing storytelling techniques demonstrated improved audience retention, while experimental and dynamic formats on TikTok outperformed static, lecture-style content. Notably, content that used interactive elements such as emojis and question prompts often saw over 100% increases in user interaction, and sequencing strategies that placed narrative elements before informational segments boosted full-video viewing by a factor of ten in some cases. The review also reveals platform-specific trends, with Facebook emerging as the most frequently studied and consistently favoring narrative and visual content. Overall, the evidence underscores the superior effectiveness of narrative, dynamic, and interactive formats in enhancing engagement with educational content on social media.